PEMODELAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI DATA KEPENDUDUKAN DESA DENGAN FRAMEWORK TOGAF 9.1 DAN SOA - endra suseno (Cloud Information, 2018)
The strategic planning that will be applied concerns the information system of village government, then this system can be called as e-Government. This refers to the definition of e-Government according to the US Federal Government that the e-Government of information delivery and government online services via internet or other digital tools, in building an integrated information system required strategic planning of each village, sub-district and district / city in development, strategic planning is useful as a reference of IT that will be used to be directed and can give maximum contribution. To overcome this, modeling of information technology architecture as a guide for the development of integrated information system. The IT Governance model approach uses the TOGAF ADM Framework.The Open Group Architecture Framework (TOGAF) is a framework and method for enterprise architecture that provides a methodology for analyzing the overall business architecture. There are three commonly accepted architectural domains as part of the overall enterprise architecture. The three domains are supported by TOGAF: Architecture Development Method (ADM) that explains how to find a company / institutional / organization architecture in detail according to business needs, and this is a core part of TOGAF.Once all components in the modeling within the TOGAF ADM framework are formed then the next strategy determines which activities will form an application, which will later be integrated. In order to the entire system in communicating effectively through a network that has been established. Thus the system to be built has a service orientation. Here is an overview of Services Oriented Achitecture (SOA).The purpose of this research is to produce Enterprise Architecture Modeling, which can be used as a foundation for the development, implementation of technology and information system for the village. Designing EA-based architecture models tailored to village activities that can simplify the implementation of information systems using TOGAF ADM and SOA work frameworks. It can generate an integrated information system strategic plan as needed.